Misconception and Effect of Menstruation (Chhaupadi) and Delivery on Women’s Health in Bajura, District Nepal - Pandit, Chetraj; Singh, Anil Kumar; Parajuli, Ayuska; Pandey, Ashok (Europasian Journal of Medical Sciences, 2021)
Background: Chhaupadi is the old unscientific system in mid and far western parts of Nepal. Reproductive age women were considered unclean during the menstrual and delivery period. Invisible cultural taboos and practices were prevailing in each and every household. The objective of the study is to assess the associated factors affecting during Chhaupadi and delivery practice with their health outcome. Method: The cross-sectional descriptive study was conducted amongst 175 reproductive age women in Bajura districts of Nepal, by using multistage random sampling. Both qualitative and quantitative methods was used. All the data were entered in Ms excel and exported into SPSS 16.0. The necessary descriptive and inferential statistics was used for quantitative analysis and thematic analysis was done for qualitative analysis. Results: More than one third (38.9%) of the participants were in the age group 20-29 years. Almost all the participants were from Hindu religion. The majority (91%) of participants know about the Chhaupadi system. Almost (74%) of the participants were staying in the Chhaupadi hut during menstruation. Similarly, (78.3%) of the respondents were mentioned, they did not like the Chhau system and never like to continued. There is a significant association between health effect in women and the Chhaupadi system (p < 0.031). Conclusion: We conclude that the larger proportion of women in Bajura District still believes in old unscientific tales and Chhaupadi practices which lead to the different health problems.